2017
DOI: 10.1097/tld.0000000000000109
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of the Consequences

Abstract: Understanding the impact of the environment on the participation of people with aphasia depends on one's perspective. A long-term perspective provides a unique insight into the myriad of ways in which the environment can influence the participation of people living with aphasia over decades. In this article, the authors present the real-life story of “Hank,” who has lived with aphasia for more than 15 years. The authors consider how 2 different conceptual frameworks—the International Classification of Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The loss of forest covers, woodlands and grazing lands in the basin is caused by a number of factors included: commercial and crop-livestock mixed farming land demand expansion, massive deforestation, charcoal production, uncontrolled wild re, resettlement, overgrazing, less attention land management practices and land use policy and population pressure. Studies conducted by (Abebe et al, 2021;Nyssen et al, 2018;Teklemariam et al, 2017;Woldemeskel, 1989) reported that the establishment of roads, large commercial farms, settlement hotspot and large sugar estates frequently removal forest and woodland cover change in the Beles basin without any mitigation measures. Between 2002 and 2019, built-up areas were progressively increased and covered about 5,481.9 ha of the basin.…”
Section: Land Use and Land Cover Classi Cation Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…The loss of forest covers, woodlands and grazing lands in the basin is caused by a number of factors included: commercial and crop-livestock mixed farming land demand expansion, massive deforestation, charcoal production, uncontrolled wild re, resettlement, overgrazing, less attention land management practices and land use policy and population pressure. Studies conducted by (Abebe et al, 2021;Nyssen et al, 2018;Teklemariam et al, 2017;Woldemeskel, 1989) reported that the establishment of roads, large commercial farms, settlement hotspot and large sugar estates frequently removal forest and woodland cover change in the Beles basin without any mitigation measures. Between 2002 and 2019, built-up areas were progressively increased and covered about 5,481.9 ha of the basin.…”
Section: Land Use and Land Cover Classi Cation Accuracymentioning
confidence: 99%
“…There are several alternative methods for valuing ecosystem services (Richardson et al, 2015), which may be nearly categorized into two groups: a) the primary valuation methods, which observe economic principles such as market prices, production approaches, travel costs, opportunity costs, conjoint analysis, and replacement costs; and b) the land use proxy-based method, which uses the Bene t Transfer Approach by using the existing ESV data from one location to another of similar setting (Anley et The Peripheral (areas away from the center region) Beles basin is branded by the Ethiopian government as one of the tremendous opportunities for a national economic growth corridor (World Bank, 2008). Thus, in this basin, giant mega projects have been running such as the Grand Ethiopian Renaissance Dam (GERD) (Teklemariam et al, 2017) (Woldemeskel, 1989), and mechanized farms (Teklemariam et al, 2017). Subsequently, issues of socioeconomics and ecological dynamics, deforestation, severe land degradation, and con icts for land and water resource (Abebe et al, 2021;Annys et al, 2019;Nyssen et al, 2018) are become very critical..…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of 2015, an estimated one million people in the United States were living with aphasia, with 180,000 people acquiring the condition each year (National Institute on Deafness and Other Communication Disorders, 2015). The consequences reach beyond the verbal behavior itself, since social, professional, material, interpersonal, and educational experiences can be dramatically impacted (O'Halloran et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, frequency of aphasia increases with advancing age, from 15% (95% confidence interval (CI) 5 to 26%) in patients younger than 65 years of age to 43% (95% CI 30 to 56%) among those at least 85 years of age 6 . Post-stroke aphasia may be considered “a social condition” 7 that has considerable impact on functional recovery and societal costs. Costs for stroke-related health care exceeded $25 billion in 2007 4 .…”
Section: Introductionmentioning
confidence: 99%